Penerapan Pressure Control Valve (PCV) pada Main Gas HRSG (Heat Recovery Steam Generator) Di PT. MCTN Kota Duri: Application Of Pressure Control Valve (PCV) In Main Gas HRSG (Heat Recovery Steam Generator) at PT. MCTN Duri City - Firdaus, Agung Ridhatullah (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2021)
In this era of globalization, science and technology has developed so rapidly. No exception to industrial technology, which has developed according to the times. One important component commonly used in industrial production processes is the Control Valve, a tool used to modify fluid flow or pressure rate in a process system. In a powerplant unit, especially PLTGU, the role of the control valve is very important. Not only in regulating the amount of gas entering the combustion in the turbine, it is also needed in supplying gas in the duck burner to the HRSG so that steam can be produced with the desired amount and quality. Based on observations in the field, at PT MCTN regarding the utilization of the control valve, it is known that its use is almost in all control systems, especially in the duck burner, precisely on the main gas HRSG. In this section the gas that will enter the duck burner has a large pressure, between 350-450 psi. This gas, which will be controlled in accordance with the production target, will be made a control system known as a Pressure Control Valve (PCV) 1/3 whose value will be adjusted using the PLC from DCS by the operator. The stages in completing this research are conducting field surveys, discussions, taking and processing data and make a conclusions. The conclusions from the implementation of this research are where the gas entering the duck burner the number or value is controlled by Pressure Control Valve 1/3 subsequently used as fuel in the steam production process, so that steam can be produced with the optimum amount and quality.